(3GdYHGH GdRGNQ hGddHGH GdaGNQs - (3QVj GdOjf CHj GdaVGFd GdMSf Hf eMeO CHh GdMSf, MjOQ GdUGZGfj, J (B650 (3g` s
(3ChdgG (B:s
(3ef MQa GdOGd JHOG Hbhdg (B: (3hbdO ef GdTQGH ai Lhag EPG TQH hGdEbdjO GdeaJGM ef eGOI bfaP s
(3BNQgG (B:s
(3hbGd (B: (3bdGFO GdNjd Ci gf cQGFe hbdOJ GdMHd Ci aJdJg hGdMHd bdO hebdhO hGdbdO GdeaJhd ef aVI s
(3GdeNWhW eYLe ai GddZI Cdag dGHf GdYdbei hRjQ GdeSJYUes
(3ChQGbgG eVWQHI GdJQJjH HgG GKQ WeSs
(3fSNI QGHYIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B214s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA GdChd (B- (3bSe GdKGfi (B- (3U (B153 s
Keywords: (3GddZIs